Risk sharing, efficiency of capital allocation, and the connection between banks and the real economy - Barattieri, Alessandro; Eden, Maya; Stevanovic, Dalibor (Journal of Corporate Finance, 2020)
We propose a measure of the extent to which a financial institution is connected to the real economy. The Share of Core Assets (SCA) is a measure of the composition of assets – namely, the share of credit to the non-financial sectors (households, firms, and governments) out of total credit market instruments. We construct the SCA for more than 3700 U.S. bank holding companies. An asset weighted average of the SCA declines by 20 percentage points in the period 1995:1 to 2012:4 (from 76% to 56%); it then increases by about 10 percentage points in the period 2013:1 to 2016:4. We explore the extent to which risk-sharing among banks and efficiency of capital allocation can explain the cross-sectional dispersion of our measure, and we find that these two motives account for between 6% and 10% of the cross-sectional variation of the SCA, depending on the sample used. Finally, using a vector autoregression model (VAR), we find that an increase in the average connection between banks and the real economy increases the growth rate of the GDP.